An Anti-MRSA Phage From Raw Fish Rinse: Stability Evaluation and Production Optimization - Abd-Allah, Israa M.; El-Housseiny, Ghadir S.; Alshahrani, Mohammad Y.; El-Masry, Samar S.; Aboshanab, Khaled M.; Hassouna, Nadia A. (Frontiers in Cellular and Infection Microbiology, 2022)
Accumulating evidence has denoted the danger of resistance in tenacious organisms like methicillin-resistant Staphylococcus aureus (MRSA). MRSA, a supple bacterium that adopts a variety of antibiotic resistance mechanisms, is the cause of multiple life-threatening conditions. Approaching a post-antibiotic era, bacteria-specific natural predators, bacteriophages, are now given the chance to prove eligible for joining the antibacterial weaponry. Considering the foregoing, this study aimed at isolating bacteriophages with promising anti-MRSA lytic activity, followed by characterization and optimization of the production of the bacteriophage with the broadest host range. Five phages were isolated from different environmental sources including the rinse of raw chicken egg, raw milk, and, remarkably, the raw meat rinses of chicken and fish. Examined for lytic activity against a set of 23 MRSA isolates collected from various clinical specimens, all five phages showed relatively broad host ranges with the bacteriophage originally isolated from raw fish rinse showing lytic activity against all the isolates tested. This phage is suggested to be a member of Siphoviridae family, order Caudovirales, as revealed by electron microscopy. It also exhibited good thermal stability and viability at different pH grades. Moreover, it showed reasonable stability against UV light and all viricidal organic solvents tested. Optimization using D-optimal design by response surface methodology was carried out to enhance the phage yield. The optimum conditions suggested by the generated model were a pH value of 7, a carbon source of 0.5% w/v sucrose, and a nitrogen source of 0.1% w/v peptone, at a temperature of 28°C and a bacterial inoculum size of 107 CFU/ml, resulting in a 2 log-fold increase in the produced bacteriophage titer. Overall, the above findings indicate the lytic ability inflicted by this virus on MRSA. Apparently, its stability under some of the extreme conditions tested implies its potential to be a candidate for pharmaceutical formulation as an anti-MRSA therapeutic tool. We hope that bacteriophages could tip the balance in favor of the human front in their battle against multidrug-resistant pathogens.